Nyando Climate Smart Villages Media Visit - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
Since 2011, farmers in Nyando Climate Smart Villages have been working with researchers, development partners, and government extension agents to test a portfolio of promising climate change adaptation, mitigation, and risk management interventions. On 5th and 6th September 2013, nine local and international journalists visited farmers in these villages to document ongoing work. Photos: S. Kilungu (CCAFS)